The Oxford Cognitive Screen for use with Australian people after stroke (OCS‐AU): The adaptation process and determining cut scores for cognitive impairment using a cross‐sectional normative study. (1st September 2022) - Sanctuary, Colette; Hewitt, Luisa; Demeyere, Nele; Kankkunen, Kirsti; Oxenham, D. Vincent; Simpson, Dawn B.; Stolwyk, Renerus J.; Synn, Artemis; Webb, Sam S.; Marsden, Dianne L.
Abstract: Introduction: Two parallel versions (A and B) of the Oxford Cognitive Screen (OCS) were developed in the United Kingdom (UK) as a stroke‐specific screen of five key cognitive domains commonly affected post‐stroke. We aimed to develop the Australian versions A and B (OCS‐AU), including Australian cut‐scores indicative of impairment. We hypothesised there to be no difference in performance between the UK and Australian normative data cohorts. Methods: Our multidisciplinary expert panel used the UK pre‐defined process to develop the OCS‐AU versions A and B. We then conducted a cross‐sectional normative study. We purposively recruited community‐dwelling, Australian‐born, and educated adults; with no known cognitive impairment; representative of age, sex, education level, and living location; at seven sites (four metropolitan, three regional) across four Australian states. Participants completed one or both OCS‐AU versions in a randomised order. Australian cohorts were compared with the corresponding UK cohorts for demographics using Pearson's chi‐squared test for sex and education, and Welch two‐sample t test for age. For the cut‐scores indicating cognitive impairment, the fifth (95th) percentiles and group mean performance score for each scored item were compared using Welch two‐sample t tests. The pre‐defined criteria for retaining OCS cut‐scores had no statistically significant difference in either percentile or group mean scores for each scored item. Results: Participants ( n  = 83) were recruited: fifty‐eight completed version A [age (years) mean = 61, SD = 15; 62% female], 60 completed version B [age (years) mean = 62, SD = 13, 53% female], and 35 completed both [age (years) mean = 64, SD = 11, 54% female]. Education was different between the cohorts for version B (12 years, p  = 0.002). Cut‐scores for all 16 scored items for the OCS‐AU version B and 15/16 for version A met our pre‐defined criteria for retaining the OCS cut scores. Conclusions: The OCS‐AU provides clinicians with an Australian‐specific, first‐line cognitive screening tool for people after stroke. Early screening can guide treatment and management.